A Novel Outlier-Robust Kalman Filtering Framework Based on Statistical Similarity Measure - Huang, Yulong; Zhang, Yonggang; Zhao, Yuxin; Shi, Peng; Chambers, Jonathon A. (IEEE transactions on automatic control, 2021)
In this article, a statistical similarity measure is introduced to quantify the similarity between two random vectors. The measure is, then, employed to develop a novel outlier-robust Kalman filtering framework. The approximation errors and the stability of the proposed filter are analyzed and discussed. To implement the filter, a fixed-point iterative algorithm and a separate iterative algorithm are given, and their local convergent conditions are also provided, and their comparisons have been made. In addition, selection of the similarity function is considered, and four exemplary similarity functions are established, from which the relations between our new method and existing outlier-robust Kalman filters are revealed. Simulation examples are used to illustrate the effectiveness and potential of the new filtering scheme.